Bad kids the naughtiest children in history] - Robinson, Tony 1946- (Macmillan Children's Books, 2011)
So you're standing outside the Head Office, waiting to be told off for breaking a classroom window. You've got sweaty palms and a serious sinking feeling in your stomach. All through history, children have been getting of into some serious scrapes. And they did not often get off lightly